Development of an Interactive English E-Module for Engineering Students at Malikussaleh University - Bungsu Keumala Sari; Fidyati Fidyati; Nurlaila Nurlaila; Azmi Basri; Rayhan Farkira (ITScience (Information Technology and Science), 2025)
This study aimed to develop an interactive English e-module for Information Systems Engineering students. Research and Development (R&D) approach with the ADDIE models was implemented in this study which comprised five primary stage, namely analysis, design, development, implementation, and evaluation. In this study, the participants included experts of media and material, as well as 15 engineering students from the Information Systems program at Malikussaleh University as users. The final product was an interactive e-module containing technical English materials equipped with features such as lessons, exercises, quizzes, and evaluations. Initially, the product was designed and saved in Microsoft Word format. The file was then uploaded and edited using the Canva application. After the entire content was designed in Canva, the file was exported and uploaded to Heyzine Flipbook to produce an interactive flipbook format. Validation results indicated that the developed application received positive responses. The media and material expert provided a score of 92.3% and 87.5% (categorized as feasible), and the students gave a score of 86.75% (categorized as practical). In addition, the students’ evaluation results reached an average score of 85 (categorized as effective). Based on these findings, the English for Engineering e-module was considered feasible, practical, and effective for use in learning activities.